Fostering awareness of the pedagogical implications of World Englishes and ELF in teacher education in Italy - Vettorel, Paola; Corrizzato, Sara (Studies in Second Language Learning and Teaching, 2016)
Teacher education represents an essential step to raise awareness of the sociolinguistic changes brought about by the current pluralization of English and by its lingua franca role. Within the pre-service teacher education programs run at the Department of Foreign Languages and Literatures, University of Verona, Italy, part of the English language course focused on issues related to World Englishes (WE) and English as a lingua franca (ELF), aiming at fostering awareness of and active reflection upon their pedagogical implications. After taking into consideration recent developments in WE- and ELF-aware teacher education, we will report on findings from a research study involving trainee teachers attending the aforementioned courses for English in academic years 2012-13 to 2014-15. The main aim of the study has been to investigate whether, how and to what extent trainee teachers’ pedagogical knowledge and reasoning about a WE and ELF-informed perspective in teaching practices may undergo a change after attending these courses. Drawing upon different sets of data (questionnaires, reflections in e-learning discussion forums, interviews and final reports), the trainees’ increased awareness of and readiness to include a WE- and ELF-informed didactic approach after attending the course will be discussed, together with implications for foreign language teacher education.